Effect of bacterial inoculants on the preservation of alfalfa and whole-plant corn silages - Bolsen, K.K.; Sonon, R.N.; Dalke, B.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Inoculated and control alfalfa and corn silages were compared in pilot-scale silos. Inoculated silages for both crops had higher lactic acid contents and DM recoveries and lower values for pH, acetic acid, ethanol, and ammonia-nitrogen than controls—evidence that the inoculants produced a more efficient fermentation. These results are consistent with numerous studies that compared untreated and inoculant-treated silages over a wide range of crops and ensiling conditions in our research during the past several years.
Keywords: Beef; Silage; Inoculant; Preservation; Alfalfa; Corn